Endothelial progenitor cells in cell-based therapy for cardiovascular disease - Rodriguez-Losada, N.; Garcia-Pinilla, J. M.; Jimenez-Navarro, M. F.; Gonzalez, F. J. (Cellular and Molecular Biology, 2008)
Coronary Artery Diseases (CAD) is the first mortality cause in industrialized countries. The possibility of regenerating myocardium injured tissue using the cell therapy is a promising option to regenerate cardiac tissue. Currently, a variety of adult stem/ progenitor cells are undergoing clinical evaluation, but it is very important to study and characterize the bone marrow-derived progenitor/ stem cells, the main source of cells used for human cardiac repair, before their clinical use. Bone marrow-derived endothelial progenitor cells (EPC) home sites of ischemia and differentiate into endothelial cells, increase the neovascularization of ischemic tissue. Moreover recently, it has been observed that EPC can be able to differentiate or transdifferentiate to like-adult cells resident in cardiac tissues. The characterization of phenotype EPC is complex, because express hematopoietic stem cells (CD133 and/ or CD34) and endothelial markers such as vascular endothelial growth factor receptor 2 (KDR). Several studies described subpopulation of EPC expressing CD34+D133+KDR+ phenotype in literature, but some other authors suggest other phenotype. The EPC capacity of mobilization or recruitment/ homing to ischemic tissue areas by cytokines are reviewed. Finally are described clinical studies in CAD using bone marrow-derived progenitor cells permitting human cardiac tissue repair.